A Novel Approach for Classifying Gene Expression Datasets - Mercy, A. Immaculate; Chidambaram, M (International Journal of Computer Sciences and Engineering, 2018)
Classification of Gene expression data is one of the challenging tasks in the domain of Bio-medical recognition. Working on high dimensional data sets always poses complexity on accuracy and on the computational fronts. A Novel approach for classifying the gene expression data has been proposed which paves path for better efficiency and effectiveness measure using an enhanced algorithm for analyzing the sequential patterns by use of a novel algorithm which surpasses the existing methods. This approach provides a better heuristics for working with both supervised and the semi-supervised data. The proposed methodology increases the efficiency by making use of the threshold values which has been used for pruning the data sets which gives rise to a higher confidence on the data sets. The classification thus achieved could help us understand the patterns using the prediction algorithm and then grouping them based on the class labels. This work and the technique that is to be used could serve us in predicting interesting knowledge on the input gene data set. As the data set is of high dimension it throws open the corridors for various analysis on the acquired classes and considerably alleviate the computation cost.